(untitled) (Fiep Bulletin - online, 2014)
Introduction: The problem of alcohol use has been linked to several risk factors and mortality tables in current society. On the other hand, physical education has occupied position highlights the actions of health promotion and positive health behaviors. Objective: To analyze the relationship of alcohol and Physical Education subjects in scientific articles published in journals until October 2012 in the databases SciELO and Bireme. Methodology: The research used a literature review. We also consulted the database SciELO and Bireme the beginning of October 2012. We considered the descriptors in Health Sciences: Alcohol; Physical Education. We selected 12 articles, proceeding to the reading and preparation of summary table containing: Authorship, Purpose, Methods, Results, and Relationship Alcohol/Physical Education. Results: All articles have investigated the term "alcohol" linking its use as a behavioral variable. Approximately 41% of the text has the term "physical education" as a Department and/or the researcher’s area. Proportion considering students or professionals of Physical Education and population studies. Participation in physical education classes was considered as a variable in 16.6% of articles. Discussion: The study highlights the limitations of published articles in scientific journals among study participants the terms involving alcohol and Physical Education. Similarly, none of the reviewed articles related these two variables. Conclusions: It is suggested that future work the extension of this literature review in other types of texts (dissertations, theses and articles in other languages??) as well as further investigation of these variables often related to health.